Kljubovanje materinstvu kot podedovani tradiciji in materinstvo kot odrešitev v delih Božene Víkove-Kuněticke in Jelene Dimitrijević - Kočevski, Ivana (Slavia Centralis, 2024)
This paper deals with the dual aspect of motherhood in both the novel by the Czech writer Božena Víková-Kunětická (1862–1934) Vzpoura (1901) and the novel by the Serbian writer Jelena Dimitrijević (1862–1945) Nove (1912). Although they follow a similar poetic direction, these women writers nevertheless have different approaches to depicting the same themes. While Jelena Dimitrijević portrays the situations in both the Turkish and American settings with a sharp eye, focusing mainly on interpersonal relationships and women’s behaviour and integration into society, Božena Víková-Kunětická is more concerned with the concrete problems her heroines go through (e.g. infidelity in marriage, pregnancy out of wedlock, deviation from traditions and socio-cultural conventions). Although the novels Vzpoura and Nove are very different in their artistic and content structure, their common element is the motif of girls growing up at the beginning of the 20th century and their resistance to the expectation of continuing traditional relationships within the family. In both novels, motherhood is experienced as a set of fixed and permitted acts and practises of expected behaviour that must not be violated, but motherhood can also be understood in a broader sense as it relates to the function and role of women in a patriarchal family and a conservative society. In this context, we have tried to identify comparatively similar and different elements that these authors use to describe certain problems (e.g. women’s relationship to tradition, their rebellion, their defiance and the question of their free choice).